A 3D Cell Culture Organ-on-a-Chip Platform With a Breathable Hemoglobin Analogue Augments and Extends Primary Human Hepatocyte Functions in vitro - Shoemaker, James T.; Zhang, Wanrui; Atlas, Selin I.; Bryan, Richard A.; Inman, S. Walker; Vukasinovic, Jelena (Frontiers in Molecular Biosciences, 2020)
Remarkable advances in three-dimensional (3D) cell cultures and organ-on-a-chip technologies have opened the door to recapitulate complex aspects of human physiology, pathology, and drug responses in vitro. The challenges regarding oxygen delivery, throughput, assay multiplexing, and experimental complexity are addressed to ensure that perfused 3D cell culture organ-on-a-chip models become a routine research tool adopted by academic and industrial stakeholders. To move the field forward, we present a throughput-scalable organ-on-a-chip insert system that requires a single tube to operate 48 statistically independent 3D cell culture organ models. Then, we introduce in-well perfusion to circumvent the loss of cell signaling and drug metabolites in otherwise one-way flow of perfusate. Further, to augment the relevancy of 3D cell culture models in vitro, we tackle the problem of oxygen transport by blood using, for the first time, a breathable hemoglobin analog to improve delivery of respiratory gases to cells, because in vivo approximately 98% of oxygen delivery to cells takes place via reversible binding to hemoglobin. Next, we show that improved oxygenation shifts cellular metabolic pathways toward oxidative phosphorylation that contributes to the maintenance of differentiated liver phenotypes in vitro. Lastly, we demonstrate that the activity of cytochrome P450 family of drug metabolizing enzymes is increased and prolonged in primary human hepatocytes cultured in 3D compared to two-dimensional (2D) cell culture gold standard with important ramifications for drug metabolism, drug-drug interactions and pharmacokinetic studies in vitro.